A Review of Interface Bonding Testing Techniques (Journal of Engineering, 2023)
Interface bonding between asphalt layers has been a topic of international investigation over the last thirty years. In this condition, a number of researchers have made their own techniques and used them to examine the characteristics of pavement interfaces. It is obvious that test findings won't always be comparable to the lack of a globally standard methodology for interface bonding. Also, several kinds of research have shown that factors like temperature, loading conditions, materials, and others have an impact on surface qualities. This study aims to solve this problem by thoroughly investigating interface bond testing that might serve as a basis for a uniform strategy. First, a general explanation of how the bonding strength function works and how it affects the pavement is given. The construction of various setups is then examined, and their functions are contrasted, followed by an explanation of various interface bond test procedures according to loading situations. A concept for a systematic approach to a standard assessment of asphalt interface is proposed, based on previous findings.